2021
DOI: 10.3390/cancers13133145
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase and Pluripotency Factors Jointly Regulate Stemness in Pancreatic Cancer Stem Cells

Abstract: To assess the role of telomerase activity and telomere length in pancreatic CSCs we used different CSC enrichment methods (CD133, ALDH, sphere formation) in primary patient-derived pancreatic cancer cells. We show that CSCs have higher telomerase activity and longer telomeres than bulk tumor cells. Inhibition of telomerase activity, using genetic knockdown or pharmacological inhibitor (BIBR1532), resulted in CSC marker depletion, abrogation of sphere formation in vitro and reduced tumorigenicity in vivo. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…It is also essential to consider the intrinsic phenotypic plasticity of stem-like cancer cells via spontaneous activation of one or more of the well-known pluripotency factors (OCT4, KLF4, c-MYC. ; and SOX2) [ 95 , 96 ]. In this context, the role of the CSCs’ niche is crucial, since it regulates the transition between stem and non-stem cell states.…”
Section: Cscs In Tumor Growth and Dissemination: The Quiescent And Th...mentioning
confidence: 99%
“…It is also essential to consider the intrinsic phenotypic plasticity of stem-like cancer cells via spontaneous activation of one or more of the well-known pluripotency factors (OCT4, KLF4, c-MYC. ; and SOX2) [ 95 , 96 ]. In this context, the role of the CSCs’ niche is crucial, since it regulates the transition between stem and non-stem cell states.…”
Section: Cscs In Tumor Growth and Dissemination: The Quiescent And Th...mentioning
confidence: 99%
“…It has been shown that also other ALDH enzymes are activated both in SCs and CSCs, including ALDH2*2 (with an association between alcoholism and alcohol-induced cancer risk), ALDH4A1 (activated through p53 and DNA damage), and ALDH7A1 (putatively involved in the regulation of cell cycle) ( 1 ). Furthermore, high ALDH activity, combined with high telomerase activity and the presence of ATP-binding cassette (ABC) transporter G2 (ABCG2), is considered as a universal stem cell marker ( 30 , 31 ). Indeed, a specific and widely used assay to measure ALDH activity called “aldefluor assay” has been originally used for the isolation of hematopoietic stem cells and now is commonly used for the CSCs isolation in many cancers ( 21 , 32 ).…”
Section: Aldehyde Dehydrogenases In Normal and Cancer Stem Cellsmentioning
confidence: 99%
“…In this sense, it has been demonstrated that pancreatic CSCs show longer telomeres and higher telomerase activity than bulk tumor cells, which is related to the expression of pluripotency genes (Nanog, Sox2, Oct3/4). Furthermore, it was confirmed that telomerase inhibition results in pancreatic CSC apoptosis, making this a suitable therapy against CSCs, specifically in pancreatic cancer [11]. Importantly, although telomere shortening is associated with DNA instability and cell senescence [12], it is a process observed in cancer initiation which is then followed by telomere lengthening for chromosome stabilization and tumor progression [13].…”
Section: Gcsc and The Hierarchical Model Of Tumor Progression: Functi...mentioning
confidence: 91%